Rap florido: reconhecimento artístico, amor e relações de gênero - Santos, Sandra Mara Pereira dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to analyze the way rap producers relate femininity and flowery rap. Rap is an elaborate musical genre mainly young people from the peripheries of Brazil and flowery rap is a term used in this thesis to refer to songs that address romantic relationships between men and women. To reflect on this association performed by singers among women and heterosexual love, we analyzed the songs of love and protest. These two modes of rap in his lyrics contains different dimensions of reality, because while the flowered rap comes to romantic relationships, the protest rap publishes content that aim to educate and raise awareness among young people of the suburbs. We understand that emotions are ruled by gender and power relationships in this way, as well as the flowery protest rap also reveals aspects regarding the differences and social inequalities that characterize gender relations in rap. During the research I interviewed fifteen rappers of São Paulo, I selected four of them and followed his publications on the rap on Facebook. Also, it took into account informal conversations with these artists made online through this social network. The focus of the investigation were the representations of femininity and masculinity produced by the rap lyrics that address the issue of amorous practices. Once married love and femininity appear to be inseparable in this genre, reflected in the rap there is a secondary social recognition for flowery rap against the protest. This secondary legitimacy to the woman image and love spells a reproduction of the devaluation of femininity in educators performances of this musical style. However, also exist in rap strategies against the degradation of women. We interpret that there are also forms of resistance to the hegemonic treatment of gender interactions, which are articulated in conjunction with traditional speeches. We therefore consider that the different ways of dealing with the references...

Esta pesquisa tem como objetivo analisar a maneira como produtores de rap relacionam feminilidades e rap florido. Rap é um gênero musical elaborado principalmente por jovens das periferias do Brasil e rap florido é um termo utilizado nesta tese para se referir às músicas que abordam relações amorosas entre homens e mulheres. Para a reflexão acerca dessa associação realizada pelos cantores e cantoras entre mulher e amor heterossexual, analisa-se as canções de amor e as de protesto. Essas duas modalidades de rap contém em suas letras dimensões diferentes da realidade, pois enquanto o rap florido trata de relacionamentos amorosos, o rap de protesto divulga conteúdos que têm como objetivo educar ou conscientizar os jovens das periferias. Entende-se que, as emoções são regradas por gênero e relações de poder, desta forma, assim como o rap de protesto o florido também revela aspectos que dizem respeito a diferenças e a desigualdades sociais que marcam as relações de gênero no rap. Durante a pesquisa entrevistei quinze rappers do Estado de São Paulo, selecionei quatro deles e acompanhei suas publicações sobre o rap, no Facebook. Além disso, levei em consideração conversas informais com esses artistas feitas on-line por meio desta rede social. O foco da investigação foram as representações de feminilidades e masculinidades produzidas pelas letras do rap que abordam o tema de práticas amorosas. Uma vez que o amor conjugal e as feminilidades parecem estar indissociáveis nesse gênero musical, refletimos que no rap existe um reconhecimento social secundário para o rap florido em relação ao de protesto. Essa legitimidade secundária para a imagem de mulher e o amor explicita uma reprodução da desvalorização das feminilidades nas atuações educadoras desse estilo musical. No entanto, também, existem no rap estratégias contra a inferiorização das mulheres; interpretamos que há também formas de...
Keywords: Rap (Música); Amor na música; Relações de gênero; Love in music